THE INFLUENCE OF EXTRACURRICULAR ACTIVITIES, TEACHER TEACHING STYLES AND LEARNING MOTIVATION ON LEARNINGACHIEVEMENT IN SMA SATYA DHARMA BALUNG JEMBER - Moh. Agus Riawan; Muhammad Firdaus; Kasiman Kasiman (STIE Mandala Jember, 2019)
Every educational institution, wants every student to achieve satisfactory achievements, achievements achieved by students are the main measurement tool and hope for knowing the success of an education. To further improvestudent learning achievement, it needs several ways to support the process of achieving that goal, and among the ways that can be taken is to start the implementation of various extracurricular activities in each educational institution. Extracurricular activities are a series of programs for teaching and learning activities outside the programmed hours, which are intended to improve the perspective of students, to foster talent and interest and to serve the community. For example: in Scouting activities is a form of activity that many develop humanitarian and spiritual activities in socializing, including cleanliness of the environment, providing assistance to people who are in disasters, health and so on. The article is intended to investigate the extent to which teaching styles and student learning motivation influence partially and simultaneously on student achievement. The samples are 124studentsoutof248from class X and XI students Satya Dharma High School Balung Jember. Data obtained from questionnaires and documentation were analyzed by multiple regression techniques. The results show that the teacher's teaching style and student learning motivation contribute more to student achievement. However, learning motivation has more dominant influence on student learning achievement than the teacher's teaching style. But this research only discusses concepts and conclusions taken from the relevant researcher hypothesis before.